The Lion Encyclopedia of the Bible - Alexander, Pat, 1937- (London Bloomsbury Books, 1994)
A handbook of informative data about the people, places, and ideas in the Bible including pertinent illustrations, photographs, maps, charts, and diagrams.
Includes index.
Keywords: Holy Bible: General (3GdcJGH GdebOS(B: (3YehejGJs; Bible -- Encyclopedia